The firrst spectra for the RX J0440.9+4431 from 2m Terskol telescope - Simon, A.; Bondar, A.V.; Reshetnyk, V.M. (Advances in Astronomy and Space Physics, 2011)
We present the rst results on the spectra of Be/X-ray binary RX J0440.9+4431 obtained with the 2m Ritchey-Chretein-Coude telescope with Cassegrain Multi Mode Spectrograph (CMMS) (with R = 14000) at Terskol observatory. The Hα line pro le indicates that the new episode of the V/R variability is occuring in the system. The pro les of the Hα, Hβ and He i 7065.71, 6678.15, 5875.97 lines were analyzed and equivalent width were determined. We compared our Hα line pro le parameters with the previous results from Reig et al. (2005) and estimated characteristic time scale for disc changes as about 14 years.